PENGARUH RASIO KEUANGAN TERHADAP ALOKASI BELANJA MODAL PADA KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - Rilo Jatitmas (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
The purpose of this study was to analyze the significance of the influence of local financial independence ratio, the ratio of the area of financial effectiveness and financial efficiency ratios area partially or simultaneously to the allocation of capital expenditure on district / city in Central Java province Period 2011 - 2013. To analyze the influence of the dominant variable (the ratio of the area of financial independence, financial effectiveness ratio of regional or local financial efficiency ratio) of the capital expenditure on district / city in Central Java province Period 2011 - 2013. The results were obtained conclusion: There is a positive and significant effect of the ratio of the area of financial independence of the allocation of capital expenditure on district / city in Central Java province Period 2011 - 2013. There is a positive and significant effect of the ratio of the area of financial effectiveness of the allocation of capital expenditure on district / city in Central Java province Period 2011 - 2013. There is a positive and significant influence local financial efficiency ratio for capex at Regency / City in Central Java province Period 2011 - 2013. The results of the F test analysis we concluded there was a significant effect of local financial independence ratio, the ratio of the area of financial effectiveness and financial efficiency ratios regions simultaneously on the dependent variable, namely capex at Regency / City in Central Java province Period 2011 - 2013. Keywords: financial independence ratio of local, regional financial effectiveness ratio, the ratio of the area of financial efficiency and capex